Spectroscopic Properties of Anisole at the Air-Ice Interface A Combined Experimental-Computational Approach - Malongwe, Joseph K'Ekuboni (Langmuir : the ACS journal of surfaces and colloids, 2016)
A combined experimental and computational approach was used to investigate the spectroscopic properties of anisole in aqueous solutions and at the ice-air interface in the temperature range of 77-298 K. The absorption, diffuse reflectance, and emission spectra of ice samples containing anisole prepared by different techniques, such as slow freezing (frozen aqueous solutions), shock freezing (ice grains), or anisole vapor deposition on ice grains, were measured to evaluate changes in the contaminated ice matrix that occur at different temperatures. It was found that the position of the lowest absorption band of anisole and its tail shift bathochromically by ∼4 nm in frozen samples compared to liquid aqueous solutions. On the other hand, the emission spectra of aqueous anisole solutions were found to fundamentally change upon freezing. While one emission band (∼290 nm) was observed under all circumstances, the second band at ∼350 nm, assigned to an anisole excimer, appeared only at certain temperatures (150-250 K). Its disappearance at lower temperatures is attributed to the formation of crystalline anisole on the ice surface. DFT and ADC(2) calculations were used to interpret the absorption and emission spectra of anisole monomer and dimer associates. Various stable arrangements of the anisole associates were found at the disordered water-air interface in the ground and excited states, but only those with a substantial overlap of the aromatic rings are manifested by the emission band at ∼350 nm